Mechatronics book series – selected papers from ICOM’01, ICOM’05 and ICOM’08 - Abdul Muthalif, Asan Gani (IIUM Press, 2011)
The first, second and third International Conferences on Mechatronics (ICOM’01, ICOM’05 and ICOM’08) were organized by the Faculty of Engineering, International Islamic University Malaysia in Kuala Lumpur Malaysia in 2001, 2005 and 2008 respectively. ICOM’01 took place between 12 th to 13th February 2001 with the theme “Mechatronics-An Integrated Engineering for the new Millennium” while the ICOM’05 conference was held from 10th to 12 th May 2005 with theme “Mechatronics-Integrated Engineering for Sustainable Development”. The third conference ICOM’08 was held from 18 th to 20th December 2008 with theme “Serving humanity through intelligent Robotic Systems”. The themes were selected timely to match the challenges at the prevailing time. The diverse applications of Mechatronics are all crucial to the commercial production for sustainable growth, economic and industrial development of a nation.